TEACHERS' PERCEPTION OF THE USE OF GOOGLE CLASSROOM TO ASSESS ENGLISH SKILLS - Rita Vidyasari; Ni Putu Era Marsakawati; Luh Putu Artini (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2022)
This study aimed to describe teachers’ perception of the use of Google Classroom to assess students’ English skills and how the teachers assessed the students during online learning nowadays by using qualitative research method. The participants were 18 teachers who were teaching senior high school level in Pasuruan, East Java. Their ages were around 23 to 58 years old while answering the questionnaire. The data were collected by using open questionnaire and interview, then analysed by using narrative analysis. The results of this study showed that most teachers used Google classroom to assess students’ English skills because it was simpler and faster. This study suggests teachers use Google Classroom while assessing students’ English skills by providing more online assessments activities. The teachers are expected to use various platforms to facilitate the students. However, the students and teachers must adapt to the condition during the COVID-19 pandemic with the online learning system.